A flow-of-funds perspective on the financial crisis : volume I : money, credit and sectoral balance sheets - Winkler, Bernhard; Riet, Ad van.; Bull, Peter; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2014)
Provides a comprehensive overview of a broad range of uses of the flow of funds within the central bank community as well as in the academic field, prepared by international experts in the field. Based on the crisis experience, it offers an overview of lessons for macrofinancial analysis and financial stability.
Keywords: Business; Business enterprises -- Finance; Finance; Banks and banking; Accounting; Macroeconomics; Economic policy